Beyond Generative Intelligence: A Comprehensive Review of Emerging Artificial Intelligence Paradigms, Explainability Challenges, Ethical Risks, and Future Directions (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The artificial intelligence landscape has undergone a profound transformation from narrow, task-specific automation to sophisticated, multi-paradigm systems capable of autonomous reasoning, emotional understanding, and creative generation. This systematic literature review synthesizes 141 peer-reviewed studies published between 2018 and 2026 to map the evolution of AI paradigms beyond the dominant Generative AI breakthrough. Following PRISMA guidelines, we analyzed 4,250 initial records across six major academic databases, ultimately including 141 studies that address seven emerging AI paradigms: Generative AI, Emotional and Empathetic AI, Social AI, Agentic AI, Multimodal AI, Explainable AI (XAI), and Responsible AI. Quality assessment was conducted using a modified Mixed Methods Appraisal Tool (MMAT) with a 0–10 scoring rubric, achieving excellent inter-rater reliability (ICC = 0.87, 95% CI: 0.83–0.91). Thematic synthesis followed a rigorous three-phase approach yielding 47 first-order codes, 18 second-order descriptive themes, and 5 overarching analytical clusters. Our bibliometric analysis reveals a decisive shift from purely technical AI research to socio-technical integration, with five dominant thematic clusters emerging: Intelligence and Learning, Generative Ecosystems, Human-Centric AI, Governance and Trust, and Autonomous Systems. Key findings indicate that while Generative AI has achieved remarkable capabilities in content creation and reasoning, critical challenges persist in explainability, algorithmic bias, and governance. The Black Box problem remains a fundamental barrier to trust in high-stakes domains such as healthcare, finance, and criminal justice, despite advances in XAI techniques including SHAP, LIME, and attention visualization. Concurrently, Dark AI threats—encompassing deepfakes, AI-powered cyberattacks, autonomous weapons, and surveillance systems—pose unprecedented risks requiring urgent international governance frameworks. We propose an Integrated AI Ecosystem Framework comprising six interdependent layers: Intelligence, Creation, Human Interaction, Autonomous, Governance, and Security, with Trustworthy AI serving as the integrating principle. This framework is positioned against existing AI governance frameworks (EU High-Level Expert Group Trustworthy AI, NIST AI Risk Management Framework, IEEE Ethically Aligned Design) and uniquely integrates technical architecture, governance principles, and an evolutionary pathway from current capabilities toward AGI. However, unlike established frameworks that have undergone extensive stakeholder validation, the proposed framework remains conceptual and its empirical validation represents a key future research priority. This framework positions Generative AI as the foundation for an evolutionary pathway toward Emotional AI, Agentic AI, Cognitive AI, and ultimately Artificial General Intelligence (AGI). Our analysis identifies eleven critical research propositions addressing gaps in multimodal integration, emotional intelligence validation, agentic system safety, XAI standardization, global AI governance, and framework empirical validation. This review contributes a unified conceptual model for understanding AI's convergent evolution and provides actionable recommendations for researchers, practitioners, and policymakers navigating the transition from isolated AI capabilities to integrated, trustworthy, human-centric AI ecosystems.